The Old and the New Jew: Changes in the Understanding of Masculinity and Zionist Pioneer Movements in Moravia - Bartáková, Daniela (Dějiny – teorie – kritika, 2014)
The Jewish Diaspora and Jewish men have often been presented as politically weak, powerless, and thus effeminate. This led to a sexual interpretation of the Diaspora as an unhealthy, physically weak, and unmanly entity. In this view, the Diaspora could be contrasted with ‘normality’, i.e., physical power and activity dominating not only the family life but also the public sphere and politics, with society where a man is fully in charge of his sexuality and emotions. Th ese negative stereotypes, the ‘effeminate’ characteristics were often applied to diaspora Jews not only by anti Semites but also by Zionists. Zionist movements viewed themselves as playing a signifi cant role in ‘healing’ the progressive degeneration of the Jewish nation. Activities of the Jewish pioneers were supposed to overcome the feminine weakness of the Diaspora and strengthen the vision of a collective, nation-based, and masculine citizenship.